Pemanfaatan Media Pembelajaran Berbasis Video dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam Siswa Kelas III SDN 005 Bontang Utara Tahun Pelajaran 2023/2024 - Alfin, Muhammad Yusri; Syamsiar, Syamsiar (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2024)
This research on the use of video-based learning media in improving Islamic Religious Education learning outcomes for class III students at SDN 005 North Bontang for 2023/2024. The main objective of the research is to determine the use of video-based learning media in improving Islamic religious education learning outcomes and to determine the increase in Islamic religious education learning outcomes by using video-based learning media. The method used is qualitative, with interviews as a data collection technique. Based on interviews with Islamic Religious Education teachers, it was found that the use of videos was well planned, involving the preparation of devices such as laptops and projectors. Videos are used to create more engaging and interactive learning, which significantly increases student focus and enthusiasm. Interviews with students show that videos help them understand concepts that are difficult to understand through text or images. The use of videos also contributes to increasing students' abilities in practicing ablution and memorizing prayers. The research results show that video media is effective in improving Islamic Religious Education learning outcomes, providing a positive impact on students' understanding and skills in these lessons. The conclusion of this research is that the use of video media has proven effective in improving students' understanding and learning outcomes, as well as increasing their interest and motivation. Video-based learning media is an effective and efficient innovation to be implemented in class III at SDN 005 North Bontang.